2002
DOI: 10.1017/s0013091500000936
|View full text |Cite
|
Sign up to set email alerts
|

On the Main Invariant of Elements Algebraic Over a Henselian Valued Field

Abstract: Let v be a henselian valuation of a field K with value group G, letv be the (unique)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The following already known lemma is proved in [1,Lemma 2.2]. For reader's convenience, we prove it here.…”
Section: Preliminary Resultsmentioning
confidence: 87%
“…The following already known lemma is proved in [1,Lemma 2.2]. For reader's convenience, we prove it here.…”
Section: Preliminary Resultsmentioning
confidence: 87%
“…To see that any monic irreducible polynomial over K is a non-trivial lifting of some monic irreducible polynomial over the residue field of w, we use the notion of distinguished pairs which was introduced by Popescu and Zaharescu [21], for local fields in 1995 and was later generalized to arbitrary henselian valued fields (cf. [1] and [3]). Definition 1.7.…”
Section: Notations Definitions and Main Resultsmentioning
confidence: 99%
“…Later, this work was generalized by Aghigh et al (cf. [1]- [4]) to henselian valued fields. The notion of saturated distinguished chains is used to find results about irreducible polynomials and to obtain various invariants associated with elements of K. Recently Jakhar and Sangwan in [10], established a connection between distinguished pairs and key polynomials over a residually transcendental extension of v. In this paper, we associate distinguished pairs with abstract key polynomials over an extension w of v to K(X).…”
Section: Introductionmentioning
confidence: 99%
“…Then by the strong triangle law, we have Lemma 3.2. Let g 0 w 0 0 g 1 w 1 1 g n w n n be a strict system of polynomial extensions over a henselian valued field K v and 1 be roots of g n g n−1 , respectively, such that v − 1 = K , with K defined by (1). If v g n > v g n 1 for some in K, then there exists a K-conjugate of such that v − > K Proof.…”
Section: Corollary Let Be As In Lemma 2d Thenmentioning
confidence: 99%
“…Popescu and Zaharescu [9], Ota [8], and Aghigh and Khanduja [1,2] have shown that one can associate several invariants to a defectless polynomial by means of complete distinguished chains defined below.…”
Section: Introductionmentioning
confidence: 99%